Compact dual-band millimeter-wave antenna for 5G WLAN. Issue 8 (26th October 2022) - Jose, Melvin Chamakalayil; Radha, Sankararajan; Sreeja, Balakrishnapillai Suseela; Gulam Nabi Alsath, Mohammed; Kumar, Pratap
Abstract: This paper presents a novel compact dual-band printed antenna with an omnidirectional radiation pattern for 5G WLAN. The antenna element comprises a star-shaped patch with six disc-shaped elements at the top and a defected ground structure at the bottom, having a radius of 3.77 mm for both. The proper feeding point and alignment with its element parameters help to achieve good impedance matching. The proposed antenna has a single center feed, a low profile, and a straightforward compact structure without any feeding complexity. A high reception fidelity antenna with comparable bandwidth and moderate gain is presented. The prototype radiator was printed on a 4 mm radius and a 1.6 mm thick dielectric substrate (Rogers RT/Duroid 5880), with a dielectric constant of 2.2. The designed antenna is fabricated and measured to validate the simulation result. The measured impedance bandwidth of 1.3 GHz (27.5–28.8 GHz) and 2.2 GHz (32.45–34.65 GHz) with a respective measured gain of 1.1 and 3.2 dBi are achieved at 28 and 34 GHz. The simulated radiation efficiency of above 95% is achieved for both bands. A good agreement between simulated and measured results of the proposed work shows that the proposed antenna is suitable for 5G short-range WLAN communications.